Feminism Study of the Novel “Catatan Juang” by Fiersa Besari - Marfuah Laswaniyah (Journal Corner of Education, Linguistics, and Literature, 2021)
This study aims to explain the feminism of the Suar character in the novel “Catatan Juang” by Fiersa Besari in terms of liberalist feminism and post-modern feminism. This research method is a qualitative descriptive method. The source of data in this research is the novel "Catatan Juang" by Fiersa Besari. The research data is in the form of the depiction of the main character in the novel. The results of this study indicate that,1) the liberal feminism of the Suar character who wants to be considered equal to men through strengthening in the public space, and 2) the post-modern feminism of the Suar character which shows the equality of men and women based on language and thought patterns.